α1D-Adrenergic receptor insensitivity is associated with alterations in its expression and distribution in cultured vascular myocytes - Fan Lin-lin; Ren Shuang; Zhou Hong; Wang Ying; Xu Ping-xiang; He Jun-qi; Luo Da-li (Acta Pharmacologica Sinica, 2016)
Aim: It is unclear why α1D-adrenergic receptors (α1D-ARs) play a critical role in the mediation of peripheral vascular resistance and blood pressure in situ but function inefficiently when studied in vitro. The present study examined the causes for these inconsistencies in native α1-adrenergic functional performance between the vascular smooth muscle and myocytes. Methods: The α1-adrenergic mediated contraction, Ca2+ signaling and the subcellular receptor distribution were evaluated using the Fluo-4, BODIPY-FL prazosin and subtype-specific antibodies. Results: Rat aortic rings and freshly dissociated myocytes displayed contractile and increased intracellular Ca2+ responses to stimulation with phenylephrine (PE, 10 μmol), respectively. However, the PE-induced responses disappeared completely in cultured aortic myocytes, whereas PE-enhanced Ca2+ transients were seen in cultured rat cardiac myocytes. Further studies indicated that α1D-ARs, the major receptor subtype responsible for the α1-adrenergic regulation of aortic contraction, were distributed both intracellularly and at the cell membrane in freshly dispersed aortic myocytes, similar to the α1A-AR subcellular localization in the cultured cardiomyocytes. In the cultured aortic myocytes, however, in addition to a marked decrease in their protein expression relative to the aorta, most labeling signals for α1D-ARs were found in the cytoplasm. Importantly, treating the culture medium with charcoal/dextran caused the reappearance of α1D-ARs at the cell surface and a partial restoration of the Ca2+ signal response to PE in approximately 30% of the cultured cells. Conclusion: Reduction in α1D-AR total protein expression and disappearance from the cell surface contribute to the insensitivity of cultured vascular smooth muscle cells to α1-adrenergic receptor activation.